Climate change intensifies the drought vulnerability of river basins: a case of the Magat River Basin. Issue 3 (13th March 2023) - Felipe, Alvin John B.; Alejo, Lanie Alejandro; Balderama, Orlando F.; Rosete, Elmer A.
Abstract: The socioeconomic impact of climate change on the drought vulnerability of a significant agricultural river basin in the Philippines, the Magat River Basin (MRB), was assessed using the AHP-entropy approach and GIS techniques. The different indicators of drought vulnerability dimensions have been evaluated and the results of this study imply that the current drought susceptibility of MRB is at 1.9–3.39 min–max scale or from low to above moderate, where the basin's sensitivity and exposure account for 57 and 31% of the total vulnerability, respectively. And that the resulting adaptive capacity has a mitigating factor of only 12%, thereby construed to be very low. The Santa Fe and Subbasin 2 sub-watersheds are identified to be moderately susceptible to drought with an average rating of 3.1 and 3.25, respectively. Meanwhile, the average drought vulnerability rating of other subbasins is between 2.08 and 2.91, which is from a low to an approximately moderate level. The overall drought susceptibility of the basin is projected to increase due to climate change under future climate scenarios up to 30% (High) of the current level. Catalyzing effective policies and climate change governance are highly encouraged to further improve mitigation and adaptation measures. HIGHLIGHTS: GIS-based socioeconomic assessment and benchmarking of the impacts of drought on Magat River Basin. The entropy and AHP techniques of multi-criteria decision-making were used to appraise the corresponding weight of drought indicators. Based on the future changes in rainfall and temperature, the vulnerability of MRB for the Mid- and Late-21st century was projected to increase by about 30% under RCP 4.5 and 8.5 scenarios. Graphical Abstract